PREVALENSI GLAUKOMA SUDUT TERBUKA PRIMER DI RSUP SANGLAH PERIODE JUNI 2017 – JUNI 2018 - Gde Aditya Putra Deva; Ni Made Ari Suryathi; I Made Agus Kusumadjaja (Universitas Udayana, 2020)
ABSTRACT Primary Open Angle Glaucoma (POAG) is often referred to as